Modelling the stakeholder environment and decision process in the U.S. higher education system - Saurbier, Ann (Business, Management and Economics Engineering, 2021)
Purpose – As higher education continues to be buffeted by challenges, college and university leaders must find a way to respond to these environmental forces. In the United States, accreditation plays an increasing role in the quality control and improvement process. The goal of this research is to gain a deeper understanding of this decision environment, and the stakeholders within that system, such that American higher education institutions may set and achieve goals more effectively. Research methodology – Grounded theory is utilized to create a conceptual framework depicting the American higher education stakeholder system. In addition to placing the actors within the system, this research is also designed to generate a stakeholder-focused institutional decision process model. Findings – When viewed in a systemic context, the accreditation process assumes a unique placement among the other critical stakeholders. With this understanding, higher education leaders may better understand, balance, and integrate the concerns of their various stakeholders, in a stakeholder-focused decision process. Research limitations – While integrating multiple theories, to depict the American higher education stakeholder system and a stakeholder-focused decision process, this research does not operationalize or undertake the empirical testing of these theoretical models. Practical implications – The influence of the dynamic external environment and the accreditation process combine to create extremely challenging decision-making conditions for higher education leaders. The ability to improve and balance the quality and ethical nature of decisions that impact their various stakeholders may assist these leaders in more accurately meeting both their institutional goals and the public good goals of higher education. Originality/Value – This study specifically seeks to integrate multiple theoretical constructs within the American higher education environment and accreditation process. The creation of a theoretical model that depicts not only the stakeholder environment but also a stakeholder-focused decision process may assist all higher education institutions.